Mucinous cystadenoma of the urachal: A case report - Yuyun Wu; Ziye Huang; Guang Wang; Chaohua Deng (Urology Case Reports)
This study reports a rare case of a mucinous cystic tumor of the urachus with low malignant potential in a 77 - year - old male, aiming to explore its diagnosis and treatment strategies. The patient had an accidental finding of a 10.7 × 4.8 cm cystic mass in the urachus during an abdominal CT scan for pneumonia. Pathological examination after complete laparoscopic resection showed cystic tumor cells with mucus accumulation. Immunohistochemistry indicated positive Ki67 (+60 %) and MUC2. Conclusion: The diagnosis of this tumor depends on pathological examination. Surgical treatment requires complete resection and prevention of mucus spillage.